STRATEGI KOMUNIKASI POLITIK BAWASLU KABUPATEN TUBAN DALAM PENCEGAHAN SENGKETA PILKADA 2020 ERA PANDEMI COVID-19 - Totok Hariyono; M. Arifin (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2021)
Bawaslu of Tuban Regency is an institution in charge of overseeing the course of Regional Head Elections as mandated by law. In addition, Bawaslu of Tuban Regency also has the authority to prevent and handle disputes in the election process. In preventing disputes, the process certainly cannot be separated from the political communication implemented by Bawaslu of Tuban Regency. This research is a descriptive qualitative type that uses the interview method and document study in collecting research data. The results showed that in preventing disputes in the election process, Bawaslu of Tuban Regency used formal, informal, vertical and horizontal political communication patterns. The use of this communication pattern is based on the complex dynamics faced by Bawaslu of Tuban Regency.